Circulating Tissue Inhibitor of Metalloproteinase-4 levels are not a Predictor of Preeclampsia in the period between 20 and 25 Weeks of Gestation - Valeria Cristina Sandrim; Jackeline Machado; Heloisa Bettiol; Marco Antonio Barbieri; Viviane Cunha Cardoso; Ana Carolina Palei; Ricardo Carvalho Cavalli (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract Objective To evaluate whether the circulating level of tissue inhibitor of metalloproteinase- 4 (TIMP-4) in the period between 20 and 25 weeks of gestation is a predictor of preeclampsia. Methods We have performed a case-control study, nested in a prospective study cohort in Ribeirão Preto, in the state of São Paulo, Brazil. Of the 1,400 pregnant women evaluated between 20 and 25 weeks of gestation, 460 delivered in hospitals outside of our institution. Of the 940 pregnant women who completed the protocol, 30 developed preeclampsia. Healthy pregnant women (controls, n = 90) were randomly selected from the remaining 910 participants. From blood samples collected between 20 and 25 weeks of gestation, we performed a screening of 55 angiogenesis-related proteins in 4 cases and 4 controls. The protein TIMP-4 was the most differentially expressed between cases and controls. Therefore, wemeasured this protein in all cases (n = 30) and controls selected (n = 90). Results There were no differences in the plasma TIMP-4 levels of cases compared with controls (1,144 263 versus 1,160 362 pg/mL, respectively; p > 0.05). Conclusion Plasma TIMP-4 levels were not altered at 20 to 25 weeks of gestation, before the manifestation of clinical symptoms; therefore, they are not good predictors of the development of preeclampsia.